2007
DOI: 10.1108/10650740710742736
|View full text |Cite
|
Sign up to set email alerts
|

Course management software adoption: a diffusion of innovations perspective

Abstract: PurposeThe purpose of this study is to explore the adoption of course management software (CMS) among faculty in a nursing program in order to better understand the consequences that result from adoption decisions.Design/methodology/approachA case study approach was taken using a component of diffusion of innovations theory as a framework for exploring the research questions.FindingsDiffusion of innovations theory suggests there are three dimensions of consequences that should be analyzed: desirable versus und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Rather, they integrate CMS features into their teaching approach gradually. Kilmon and Fagan (2007) studied the nature of CMS adoption among faculty in a nursing program. Their findings contained the following three themes on CMS: (1) CMS facilitates course management, (2) CMS improves the communication among students and instructors while used it as a supplement to classroom instruction, and (3) CMS is easy to be used and needs only a minimal training and technical support.…”
Section: The Adoption Of Course Management Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, they integrate CMS features into their teaching approach gradually. Kilmon and Fagan (2007) studied the nature of CMS adoption among faculty in a nursing program. Their findings contained the following three themes on CMS: (1) CMS facilitates course management, (2) CMS improves the communication among students and instructors while used it as a supplement to classroom instruction, and (3) CMS is easy to be used and needs only a minimal training and technical support.…”
Section: The Adoption Of Course Management Systemsmentioning
confidence: 99%
“…For the faculty who are teaching a large classroom‐based course, CMS can be easily used as a communication channel to all students in that class. According to the research findings of Kilmon and Fagan (2007), most faculty members adopted CMS did not need a formal training, or just took a short training session if needed. Although CMS offers many advantages for course management, a person who uses CMS does require advance planning, good organization skills, more attention to details, and improved written communication skills.…”
Section: The Adoption Of Course Management Systemsmentioning
confidence: 99%
“…Most studies on innovations have used two separate perspectives for analysis-adoption and diffusion 4,26 .…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…A follow-up suggestion was to examine the consequence of adoption in environments less favorable than that of this study (Kilmon and Fagan, 2007). For example, use of non-adopting faculty or a technology tool that is more complex might provide an important contrast to these findings.…”
Section: Learning Benefits and Teaching Stylesmentioning
confidence: 99%
“…It was also found that learning was facilitated by interactions between students and content as well as instructors which the LMS promulgated (Liao, 2005). Kilmon and Fagan (2007) examined the consequences that result from a decision to adopt an innovation. The design was a case study based on the DOI framework.…”
Section: Learning Benefits and Teaching Stylesmentioning
confidence: 99%